Re‐use of fruit waste to produce new fibers - Condor, Lizbet (2017)
This research seeks to address the current problem in reference to the growing waste of perishable foodstuffs caused by deficiencies in distribution due to the various mishaps on the transport routes from the provinces to the capital, which is the main market for farmers. With the analysis of selected fruits, characteristics and uses of the reuse of these will be demonstrated in reference to the replacement of leather, generating a sustainable and economic product.